Reliability study of photovoltaic PV configurations - Wang, Qingsheng. (2011)
One of the most promising sources of renewable energy is the direct conversion of solar energy into power. For a large scale photovoltaic system, it consists of many solar panels which is connected in series, parallel or a combination of both. Because PV power supply system is not yet large-scale production, there are still a lot of design defects and failures. These caused the reliability index of overall photovoltaic power supply system is low. Thus the system configuration plays an important factor in determining the reliability of overall system. In this project, feasible configurations of photovoltaic system at the given number of solar panels is evaluated and analyzed. As a result, the optimal configuration of a PV system which has the best reliability and the longest useful time is obtained.